Sarcolab pilot study into skeletal muscle's adaptation to long-term spaceflight. (December 2018) - Rittweger, Jörn; Albracht, Kirsten; Flück, Martin; Ruoss, Severin; Brocca, Lorenza; Longa, Emanuela; Moriggi, Manuela; Seynnes, Olivier; Di Giulio, Irene; Tenori, Leonardo; Vignoli, Alessia; Capri, Miriam; et al.
Abstract Spaceflight causes muscle wasting. The Sarcolab pilot study investigated two astronauts with regards to plantar flexor muscle size, architecture, and function, and to the underlying molecular adaptations in order to further the understanding of muscular responses to spaceflight and exercise countermeasures. Two crew members (A and B) spent 6 months in space. Crew member A trained less vigorously than B. Postflight, A showed substantial decrements in plantar flexor volume, muscle architecture, in strength and in fiber contractility, which was strongly mitigated in B. The difference between these crew members closely reflected FAK-Y397 abundance, a molecular marker of muscle's loading history. Moreover, crew member A showed downregulation of contractile proteins and enzymes of anaerobic metabolism, as well as of systemic markers of energy and protein metabolism. However, both crew members exhibited decrements in muscular aerobic metabolism and phosphate high energy transfer. We conclude that countermeasures can be effective, particularly when resistive forces are of sufficient magnitude. However, to fully prevent space-related muscular deterioration, intersubject variability must be understood, and intensive exercise countermeasures programs seem mandatory. Finally, proteomic and metabolomic analyses suggest that exercise benefits in space may go beyond mere maintenance of muscle mass, but rather extend to the level of organismic metabolism. Muscles: Onboard exercise limits muscle loss in space Physical activity with resistive forces helps preserve muscle volume, architecture and strength in space. A team led by Jörn Rittweger from the German Aerospace Center in Cologne studied two crew members who spent six months on board the International Space Station. During the Sarcolab pilot study, one of these astronauts performed less exercise than the other. After returning to Earth, the one who trained less showed more substantial deterioration of the plantar flexor muscle in the foot—a difference detectable also at the molecular level, with lower levels of proteins involved in anaerobic and aerobic muscle metabolism. The findings highlight the need to vigorously exercise in space to limit muscle weakness. Doing so does not seem to fully prevent space-related problems, though, as evidenced by signs of muscle wasting even in the astronaut who trained regularly.